Glucose avidase immobilization by polymer matricies in supercritical carbon dioxide environment for biosensor preparation - İnoğlu, Nilay. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
In this study, immobilization of glucose oxidase (GOX) by polyurethane (PU) film and PU foam matrices using supercritical carbon dioxide (scCO2) was realized and proposed as a new technique to be used in biosensor preparations. Effects of immobilization temperature (25-50oC), pressure (1-150 bar) and time (4-72 hr) on the activity of GOX immobilized PU samples were studied. Swelling characteristics of PU samples at 40oC were also determined. Results of swelling experiments for PU films showed that, maximum surface area increased up to a soaking pressure of 100 bar and beyond this value it started to decreased. Almost no swelling was obtained for PU foams. Immobilization experiments showed that, enzymatic activity increased up to 100 bar. As pressure increased from 80 to 100 bar, the activity increased almost 75 per cent; whereas further increase in pressure to 150 bar caused a 34 per cent decrease. It was also seen that the activity values were inversely proportional to temperature. The activities obtained at 80, 150 and especially 100 bar were 52, 74 and 166 per cent higher, than the highest value obtained without using supercritical process which shows the positive effect of supercritical process. Moreover, activity values determined for PU films were higher than the ones of PU foams. The difference may be attributed to the better swelling capability of films and indicates that PU films serve as better immobilization matrices than PU foams. For PU film and PU foam, the pseudo-optimal conditions yielding maximum activity were determined as 100 bar-25oC and 100 bar- 40oC respectively.
Keywords: Biosensors.; Carbon dioxide.; Polyurethanes.; Supercritical fluid extraction.